ANALISIS SISTEM AKUNTANSI KAS PADA PT. BANK RAKYAT INDONESIA KANTOR CABANG PALEMBANG A. RIVAI - Kuswara, Muhammad Fauzan (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2024)
Currently, particularly critical during the data information or cash data processes per period, which require precise accuracy. Data input errors by employees, whether intentional or unintentional, can also result in discrepancies in financial reports. Moreover, without stringent internal controls, unethical employees may have opportunities to commit irregularities. If these risks are not effectively managed, they can impede routine operational activities and erode customer trust in the bank. The objective of this research is to analyze the effectiveness of computerization in the financial and accounting departments in improving the efficiency of cash receipt and disbursement systems. The analytical method employed in this research is descriptive analysis, which involves describing the cash receipt and disbursement procedures through observation, interviews, documentation, and analyzing the accounting information system for cash receipt and disbursement. The research findings indicate that the accounting information system at PT. BRI KC Palembang A. Rivai is implemented based on standard operational control procedures for both cash receipt and disbursement transactions. The operational procedures involve various parties, including customers, tellers, AMO, ADK officers, with final approval and oversight from the branch manager and audits conducted by regional office supervisors. The accounting records used are based on relevant documents for cash receipt and disbursement, all of which are entered into the BRI information system (BRINEST) database based on data from the All Accepted Transaction Report (AATR).